1992
DOI: 10.1200/jco.1992.10.7.1044
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of HER-2 oncoprotein expression in breast cancer: a 30-year follow-up.

Abstract: HER-2 oncoprotein expression has long-term prognostic significance for predicting poor survival in BC, and it has an independent prognostic value among patients who presented with axillary nodal metastases. This result is contradictory to the argument that HER-2 expression is only a marker for drug resistance because the patients were not given adjuvant drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
4
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(131 citation statements)
references
References 14 publications
4
117
4
5
Order By: Relevance
“…The HER2/neu oncoprotein is a transmembrane glycoprotein receptor sharing sequence homology with the epidermal growth factor receptor [15,16]. Amplification of HER2/neu, occurring in approximately 15-30% of human primary breast cancers, is associated with a higher probability of disease relapse [17,18]. Braun et al [14] using a double labeling assay showed that 60% of the studied patients had DTCs which co-expressed the cytokeratin-18 (CK-18) and HER2/neu molecules; the detection of these CK-18?/HER2?…”
Section: Introductionmentioning
confidence: 99%
“…The HER2/neu oncoprotein is a transmembrane glycoprotein receptor sharing sequence homology with the epidermal growth factor receptor [15,16]. Amplification of HER2/neu, occurring in approximately 15-30% of human primary breast cancers, is associated with a higher probability of disease relapse [17,18]. Braun et al [14] using a double labeling assay showed that 60% of the studied patients had DTCs which co-expressed the cytokeratin-18 (CK-18) and HER2/neu molecules; the detection of these CK-18?/HER2?…”
Section: Introductionmentioning
confidence: 99%
“…In nude mice (Warri et al, 1991) tamoxifen treatment was associated with enhanced expression of c-erbB2 and growth arrest. This is surprising since amplification and overexpression of c-erbB-2 usually correlate with poor prognosis and increased growth rate (Tsuda et al, 1990;May et al, 1990;Toikkanen et al, 1992). In contrast, the studies of Le Roy et al (1991) showed lower cerbB-2 RNA levels in a tamoxifen-treated group of patients in comparison with an untreated group, but only in a subset of ER-negative tumours, whereas there was no difference in the ER' group.…”
Section: Discussionmentioning
confidence: 98%
“…Specific molecular changes previously described in breast cancer cells included reduced HLA 1 (Wright et al, 1992), amplified ERBB-2 (Bargmann et al, 1986;Gusterson et al, 1992;Toikkanen et al, 1992) and uniformly distributed, underglycosylated mucin (Girling et al, 1989;Finn et al, 1995). Changes in HLA I and ERBB-2 were not detected in British Journal of Cancer (1998) MCF-IOF cell series.…”
Section: Discussionmentioning
confidence: 92%
“…A handful of molecular changes have been previously associated with breast cancer, including reduced level of class I major histocompatibility antigen (HLA I) (Wright et al, 1992), amplification of ERBB-2, which is a transmembrane tyrosine kinase and a member of the epidermal growth factor receptor family (Bargmann et al, 1986;Gusterson et al, 1992;Toikkanen et al, 1992), prolific and uniform expression of mucin as well as underglycosylation of these mucin molecules to expose the protein backbone (Girling et al, 1989;Finn et al, 1995). Changes in HLA I and mucin may be the consequence rather than the cause of neoplastic progression.…”
mentioning
confidence: 99%